Estudio de prefactibilidad para la instalación de una planta industrial productora de conservas de pescados Doncella y Boquichico - Aguilar Saavedra, Alex Enrique (2020)
The present research seeks to evaluate the feasibility in the production of canned fish for two types of species: Doncella and Boquichico. This idea was born as a result of the acceptance that both species have had in recent years. People, especially those who consume fish frequently, are precisely those who most value the type of meat of fluvial or maritime species, in addition to their nutritional contribution. The Doncella and the Boquichico have managed to delight many of their consumers for their good and the excellent texture of their meats. Through this research, we seek to offer these species in a different presentation from te ones that already exist. In addition, we want to promote and get more people to know both Peruvian species and to include them in their daily diet. Finally, it is expected that this product may complement the supply of fish, especially in periods of closure when they can not be consumed as fresh fish.